The practical guide to waste management law with a list of abbreviations and acronyms, useful websites and relevant legislation - Hawkins, Richard, 1930-2014 (Thomas Telford, 2004)
The aim of this practical guide is to provide public and private sector practitioners, some of whom are working for a waste awareness certificate and who do not have legal training, with an understanding of operational waste management law and the practical implications of non-compliance.